Civil Voices and Military Echoes: Media Responses to the Army’s Political Intervention In 1952 - Arifin Suryo Nugroho (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Muhammadiyah Purwokerto, 2025)
This article examines the responses of the mass media to the Indonesian Army’s political intervention during the 17 October 1952 Incident, employing a historical research method that includes the stages of heuristics, source verification, interpretation, and historiography. The incident not only shook civil–military relations but also ignited fierce debates among the Indonesian press in the early 1950s. The mass media, serving as the main instrument of public opinion formation, were divided into two major camps: the Merdeka newspaper on one side, and Indonesia Raya and Pedoman on the other. Under the leadership of B.M. Diah, Merdeka firmly condemned the Army’s actions, viewing them as a coup attempt against the constitutional government and warning of the dangers of military authoritarianism to democracy. Conversely, Indonesia Raya and Pedoman perceived the military intervention as a reaction to an unstable parliamentary system plagued by political intrigues. Through an analysis of editorials, opinion pieces, and the personal connections between press figures and the military, this study reveals that the divergent stances of the media reflected ideological tensions between civil supremacy and military political legitimacy—serving as an early mirror of civil–military dynamics in Indonesia’s post-independence political history.